Analysis of Casting Time on Jointed Plain Concrete Pavement - Noor, Rusandi; Muhammad, Feri; Zulkarnain, Isnaini (International Journal of Engineering and Technology, 2019)
The purpose of this study is to focus on numerical procedures for the best timing of jointed plain concrete pavement casting, which has resulted in an effective length and thicknees ratio of pavement. The aim of the study can be achieved by developing a computer simulation model that can estimate pavement strength of the actual state with loads such as shrinkage, creep, and vehicle load. The research develop of each creep coefficient and shrinkage strain based on observed data in the early age. This research will be varied input of soil parameter in the form of subgrade reaction (k), value of subbase stabilized cement with thicknees 15 cm is 4826,33 MPa. Combination simulation result shown, the comparison of concrete thicknees (H) and concrete length (L) for nigth casting k=13MPa/m, minimum thickness (H)=L/9.94; for k=27MPa/m, minimum thickness (H)=L/10.08; k=55MPa/m, minimum thikness (H)=L/10.08; k=83MPa/m, minimum thickness (H)=L/10.38 for daytime casting k=13MPa/m, minimum thickness (H)=L/8.62; k=27MPa/m, minimum thickness (H)=L/9.99; k=55MPa/m, minimum thickness (H)=L/9.15; k=83MPa/m minimum thickness (H)=L/9.33. Casting time is an important factor affecting the dimensional and shape accuracy concrete pavement. This paper can provide a theoritical basis for developing jointed plain concrete casting procedure.Â Â